Molecular Detection of Fungi from Fish Lakes in Wasit Province (Journal of Pharmaceutical Negative Results, 2022)
This study will look for the fungus Saprolegnia parasitica from fish in several lakes in the Wasit Province that are associated with fish farming (carp). Sixty samples were collected from several organs, including the gills, skin, and eyes. Which bears the following signs (skin blisters, gills that have turned dark gray from necrosis, and a blow to the eyes led) were collected from lakes in the Wasit Province during the period (October 2021- December 2021). It might take a lot of time and effort to isolate and identify fungi using traditional procedures. The fish parasite Saprolegnia parasitica may be identified using DNA-based fungal detection techniques (carp). According to the results of this PCR study, fish do not harbor this fungus. As a result, it manifests as deficiencies. It therefore shows itself as inadequacies. Poor management, including a poor feed, insufficient oxygen application, and unclean water, were to blame for the dead fish.